2021
DOI: 10.1080/10717544.2021.1965675
|View full text |Cite
|
Sign up to set email alerts
|

Nanocubosomal based in situ gel loaded with natamycin for ocular fungal diseases: development, optimization, in-vitro , and in-vivo assessment

Abstract: Natamycin (NT) is a synthetic broad-spectrum antifungal used in eye drops. However, it has low solubility and high molecular weight, limiting its permeation, and generally causes eye discomfort or irritation when administered. Therefore, the present study aimed to develop an ophthalmic in situ gel formulation with NT-loaded cubosomes to enhance ocular permeation, improve antifungal activity, and prolong the retention time within the eye. The NT-loaded cubosome (NT-Cub) formula was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…Also importantly, it was easy to perfuse and reduced the frequency of perfusion, thus making it more acceptable to the patient [96]. Table 3 [93][94][95][96][97][98][99] lists pH-sensitive in situ gel eye drop delivery systems in the application of the anterior and posterior segments of the eye.…”
Section: Ph-sensitive In Situ Gel Eye Drop Delivery Systemsmentioning
confidence: 99%
“…Also importantly, it was easy to perfuse and reduced the frequency of perfusion, thus making it more acceptable to the patient [96]. Table 3 [93][94][95][96][97][98][99] lists pH-sensitive in situ gel eye drop delivery systems in the application of the anterior and posterior segments of the eye.…”
Section: Ph-sensitive In Situ Gel Eye Drop Delivery Systemsmentioning
confidence: 99%
“…The flow rate of the mobile phase was performed at 1 mL/min, and the FI was eluted at 3.4 min. The steady-state flux (Jss) for each sample was calculated using the slope of the curve plot between the cumulative percentage penetrated and time (Hosny et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Stability studies were conducted after synthesis of the cubosomes and after 96 h, and there was no significant difference in the PDI or zeta potential during this period. Relative to the impact of single-component cubosomes composed of DOX DOTAGA-OA or DOTAGA-OA- 177 Lu complexes, cubosomes combining doxorubicin and the radionuclide-based complexes showed significant cellular toxicity as evaluated by the vitality of the in vitro HeLa cell lines. The stability of the cubosomes with 177 Lu was studied in PBS buffer and human serum for 24 h, and up to 86% and 78% radioactivity, respectively, was retained in the cubosomes.…”
Section: Intravenous/parenteral Routementioning
confidence: 96%
“…In comparison with the market product Alphagan s P, the in vivo analysis revealed a 4.6-fold higher AUC and a 9.1-fold rise in the mean residence time. 176 Additional studies that showed significant results include a natamycin/cubosome in situ gel, 177 a ketoconazole/cubosome gel, 178 fluconazole/cubosomal nanoparticles, 179 acetazolamide/ cubosomes, 180 dorzolamide/cubogel, 181 and latanoprost/ cubosomes. 182…”
Section: Ophthalmic Routementioning
confidence: 99%
See 1 more Smart Citation